PERANCANGAN SISTEM EVALUASI DOSEN OLEH MAHASISWA (EDOM) UNIVERSITAS MUHAMMADIYAH JAMBI BERBASIS WEBSITE - Helmina, Helmina; Santoso, Heri; Nurdin, Nurdin; Ikhsan, Muhammad (Jurnal Informatika, Sistem Informasi dan Kehutanan (FORSINTA), 2023)
Jambi Muhammadiyah University participates in evaluating lecturers. However, the evaluation process carried out was still manual, namely using paper, where the paper containing the questionnaire was circulated to students and not all students filled out and collected the questionnaire again. Assessment procedures in this way are considered less effective and efficient. This procedure has many weaknesses including the use of a lot of paper in each questionnaire distribution, the calculation of the assessment requires a longer time, and the possibility of calculation errors due to human error. Therefore an information system is needed that can overcome this problem so as to increase the effectiveness and efficiency of the process of assessing and evaluating lecturer performance. The system is built using the PHP programming language and as a database using MySQL. The method used in this study uses the waterfall method with the stages of needs analysis, system design, system implementation and system testing. The design of this system uses data collection techniques, namely observation, interviews, and document review. The expected results in this study are a website-based Lecturer Evaluation Information System that can facilitate related parties in measuring the quality standards of lecturer quality at the University of Muhammadiyah Jambi.